Penurunan Resiko Pada Departemen Key Account Management Divisi Ekspor di PT. XXX - William Gunawan; Felecia Felecia (Jurnal Titra, 2019)
PT. XXX is a custom broker company and KAM department is a department that specialized in handling all shipment requirement for PT. Y. This risk reducement is carried out for avoiding complaints from VIP customer. The activities that observed is start from when the worker receive shipment plan from PT. Y, preparing all clearance documents until the goods received by the consignee. There are 59 risky activities found and 27 were considered prioritized based on FMEA method and RPN scoring. Risk that considered prioritized if the activities has a high RPN value where the RPN is affected by probability, detection, and severity. Prioritized activites such as incorrect data in documents is considered prioritized. All prioritized activites will be given solution and documented as work instruction. All the work instructions will be socialized to every worker and if done properly it will reduce risk that occur in the company both time and financially and it will reduce 45.8% from 27 risk that prioritized from 59 risky activities.